2013
DOI: 10.3349/ymj.2013.54.3.572
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Simultaneous EEG Features during PET Studies for Childhood Partial Epilepsy

Abstract: PurposeTo demonstrate the significance of simultaneous electroencephalography (EEG) recording during 2-deoxy-2-[18F] fluoro-D-glucose (FDG)-positron emission tomography (PET) in childhood partial epilepsy.Materials and MethodsWe included 46 children with partial epilepsy who underwent simultaneous EEG during PET. We compared the epileptogenic area of several EEG features including epileptiform discharges, focal polymorphic slow waves, and electrographic seizures, with the abnormal metabolic region on PET. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Five patients had presumed interictal focal PET hypermetabolism. We believe concomitant surface EEG during PET should be considered in the presurgical evaluation of patients suffering from frequent seizures, to better interpret the FDG-PET results, as active IEDs and prominent rhythmic activity are associated with PET hypermetabolism [24,29,31]. Our results suggest that PET hypermetabolism is more commonly associated with frequent IEDs than ictal EEG.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Five patients had presumed interictal focal PET hypermetabolism. We believe concomitant surface EEG during PET should be considered in the presurgical evaluation of patients suffering from frequent seizures, to better interpret the FDG-PET results, as active IEDs and prominent rhythmic activity are associated with PET hypermetabolism [24,29,31]. Our results suggest that PET hypermetabolism is more commonly associated with frequent IEDs than ictal EEG.…”
Section: Discussionmentioning
confidence: 58%
“…A high spike count was also reported in other studies although the calculation was different [29,31]. Bansal et al [24] found FCD in all cases.…”
Section: Discussionmentioning
confidence: 63%
“…The severe group had higher values of jAIj than the mild and moderate groups, and the jAIj was positively correlated with seizure frequency in patients with hyper-or hypometabolism. Although hypermetabolism is frequently observed during the ictal state of epilepsy (32,33), it can also be observed in the absence of ictal events during tracer uptake and correlates well with regions of high spike count, suggesting a state of increased epileptogenicity (33,34). In view of the abundant sample size of patients with interictal hypermetabolism, we assume that the jAIj value on 18 F-FDG PET images in patients with hypermetabolism could be affected by the clinical severity and seizure frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities on EEG were classified by lobe and correlated with the abnormal PET region. The frequency of EEG epileptiform discharges convergent with the PET findings was analyzed for each patient and recorded as a spike count of either greater or less than 10 spikes/minute, a measure used in a prior study . In addition, the coexistence of focal or regional delta‐theta slowing was also noted.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, PET hypermetabolism is reported only rarely and its significance is unclear . Furthermore, there are no studies of seizure outcome after surgical resection of the hypermetabolic PET regions.…”
mentioning
confidence: 99%